2020
DOI: 10.1002/ldr.3587
|View full text |Cite
|
Sign up to set email alerts
|

Elevational differences in the net primary productivity response to climate constraints in a dryland mountain ecosystem of northwestern China

Abstract: Dryland mountain ecosystems regulate global terrestrial carbon cycling and show high sensitivity to climate variability. The Qilian Mountains (QLMs) typify dryland mountain ranges in northern temperate belts and offer fundamental ecosystem services including forage production and water conservation. However, dominant controls on the interannual trend and variability of net primary productivity (NPP) in this region are unknown. Thus, we examined magnitude and direction of the NPP trend and quantified NPP sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 75 publications
3
10
0
Order By: Relevance
“…We also found that an increase to decrease trend of NPP occurred in the southern part of Qinghai Province (Figure 2c), which is different with the monotonic increase trend reported by Peng, Liu, Liu, Wu, and Han (2012). The trend reversal from increase to decrease in the southern part of Qinghai Province was related to the transition of climate conditions from warm–wet to warm–dry and the heavy grazing (Jiang, Li, Shen, & Chen, 2012; Wang, 2003; Xu, Zhao, & Wang, 2020). These results indicated that the shifted trends, including decrease to increase and increase to decrease, were widely distributed in arid and semiarid areas, which was rarely reported by previous studies (He et al, 2015; Huang & Kong, 2016; Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that an increase to decrease trend of NPP occurred in the southern part of Qinghai Province (Figure 2c), which is different with the monotonic increase trend reported by Peng, Liu, Liu, Wu, and Han (2012). The trend reversal from increase to decrease in the southern part of Qinghai Province was related to the transition of climate conditions from warm–wet to warm–dry and the heavy grazing (Jiang, Li, Shen, & Chen, 2012; Wang, 2003; Xu, Zhao, & Wang, 2020). These results indicated that the shifted trends, including decrease to increase and increase to decrease, were widely distributed in arid and semiarid areas, which was rarely reported by previous studies (He et al, 2015; Huang & Kong, 2016; Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The CASA model is a remote sensing-based process model. It performs well in longterm series and large-scale estimation of NPP [31,32]. The two indispensable components in the CASA model are absorbed photosynthetically active radiation (APAR) (MJ•m −2 ) and light use efficiency (LUE) factor ε (gC•MJ −1 ) [33][34][35].…”
Section: Net Primary Production (Npp) Estimation Modelmentioning
confidence: 99%
“…Light-use efficiency (ε), which is the efficiency of vegetation to convert absorbed photosynthetic effective solar radiation into organic carbon, is a key parameter for calculating NPP [20]. It can be affected by various environmental conditions (e.g., temperature and moisture).…”
Section: Modeling 231 Casa Modelmentioning
confidence: 99%
“…where T ε1 (x, t) and T ε2 (x, t) are temperature stress coefficients, which indicate the reduction in light-use efficiency caused by temperature; W ε (x, t) is the moisture stress coefficient, which reflects the reduction in light-use efficiency caused by moisture; and ε max is the maximum light-use efficiency and is determined by the empirical method [20]. For details of the above parameters, see Table S2.…”
Section: Modeling 231 Casa Modelmentioning
confidence: 99%
See 1 more Smart Citation